A Commemorative Issue in Honor of 200th Anniversary of the Birth of Gregor Johann Mendel: The Genius of Genetics - Smýkal, Petr; von Wettberg, Eric J B (International journal of molecular sciences, 2023)
In celebration of the bicentennial of the birth of Gregor Johann Mendel, the genius of genetics, this Special Issue presents seven papers [...].
Keywords: History, 19th Century; Famous Persons; významné osobnosti; genetika; dějiny 19. století; Genetics